The Relationship Between Laparoscopic Cystectomy and Ovarian Reserve: A Systematic Review and Meta-Analysis - Primarintan, Talita Nandia (Asian Journal of Health Research, 2024)
Introduction: Laparoscopic cystectomy is the first-line recommended treatment for different ovarian cysts. Several mechanisms have been proposed to explain the negative impact of laparoscopic cystectomy on ovarian reserves, including the loss of normal ovarian tissue during cyst stripping, heat damage from electrosurgery, inflammation, and edema. The purpose of this systematic review is to synthesize and quantify the currently available research on the effect of laparoscopic cystectomy on ovarian reserve using multiple indicators. Material and Methods: The PubMed database was searched using the keywords "laparoscopic cystectomy" and "ovarian reserve," which yielded 23 papers for the final review. The Cochrane Risk of Bias tool was used to assess potential bias. Results: AMH, FSH, reserve ovarian volume, and PSV all showed significant changes at different time points after surgery, although LH and estradiol did not. AMH is the most frequently utilized and sensitive method for evaluating ovarian reserve at various time periods. Conclusion: Laparoscopic cystectomy reduces ovarian reserve across various indicators.